To analyze the intercepts of the functions \( f(x) = x^3 + 1 \) and \( g(x) = x + 1 \):
-
X-intercepts occur where the output of the function is 0 (i.e., \( f(x) = 0 \) or \( g(x) = 0 \)).
-
For \( f(x) = x^3 + 1 \): \[ x^3 + 1 = 0 \implies x^3 = -1 \implies x = -1. \] Thus, the x-intercept is \( (-1, 0) \).
-
For \( g(x) = x + 1 \): \[ x + 1 = 0 \implies x = -1. \] Thus, the x-intercept is also \( (-1, 0) \).
-
-
Y-intercepts occur where \( x = 0 \).
-
For \( f(x) = x^3 + 1 \): \[ f(0) = 0^3 + 1 = 1. \] Thus, the y-intercept is \( (0, 1) \).
-
For \( g(x) = x + 1 \): \[ g(0) = 0 + 1 = 1. \] Thus, the y-intercept is also \( (0, 1) \).
-
Since both functions have the same x-intercept of \( (-1, 0) \) and the same y-intercept of \( (0, 1) \), the true statement about the intercepts of the functions is:
Both functions have an x-intercept of \((-1, 0)\) and a y-intercept of \((0, 1)\).
Therefore, this option is correct: "Both functions have an x-intercept of (-1,0) and a y-intercept of (0,1)."